2018
DOI: 10.1016/j.foodres.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection efficacy over yeast biofilms of juice processing industries

Abstract: Membrane separation systems represent a hot - spot for biofilm formation in juice industries. Sodium hypochlorite (NaOCl) has been traditionally the disinfectant of choice; however, its effectiveness over well-established biofilms is limited. In this work the study of biofilm formation on ultrafiltration membranes was proposed. The effectiveness of cleaning and disinfection procedures commonly used in juice industry was tested on the removal and killing of cells. The species used (Rhodotorula mucilaginosa, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…are among the most common yeast species associated with UF membranes in fruit juice processing plants (Tarifa et al . ). Candida tropicalis L5, a strain previously isolated from UF membranes, strongly adheres to the surface of stainless steel, forming resistant biofilms which may confer a competitive advantage over other yeasts (Brugnoni et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…are among the most common yeast species associated with UF membranes in fruit juice processing plants (Tarifa et al . ). Candida tropicalis L5, a strain previously isolated from UF membranes, strongly adheres to the surface of stainless steel, forming resistant biofilms which may confer a competitive advantage over other yeasts (Brugnoni et al .…”
Section: Introductionmentioning
confidence: 97%
“…Candida spp. are among the most common yeast species associated with UF membranes in fruit juice processing plants (Tarifa et al 2018). Candida tropicalis L5, a strain previously…”
mentioning
confidence: 99%
“…Since microorganisms residing on textiles can have several harmful effects, it is important to avoid microbial growth or to remove established biofilms from the material. Many conventional mechanical and chemical routine methods are available to contain biofilm formation in different industrial equipment [58], but these methods do not work for every setting where reliable removal is needed, such as for biofilm removal from various types of fabrics. Therefore, in this study, once it was observed that Pseudomonas species adhere strongly to the cellulose surface, different washing formulations (based on detergent and enzymatic solutions) were tested to remove biofilms of Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…Pomegranate juice wastes are the result of the fruits squeezing process. Due to the large amounts of wastes produced in the fruit juice industry every cultivation period, this industrial activity is of social [13], economic [14,15], and ecological importance [16,17].…”
Section: Pomegranate Juice Production and Wastesmentioning
confidence: 99%